Structural changes and external vulnerabilities in the Brazilian economy within the period 1995-2009 - Rossana Rodrigues; Jo\~ao Carlos Lopes; Jo\~ao Dias; Antonio Carlos Moretto (European Regional Science Association (ERSA), 2013)
From the 1990s, the Brazilian development model went from protector of the industrial sector to the trade liberalization process, which brought the need for extensive restructuring of the productive sectors of the economy must, henceforth to confront openly the global competitors within the prevailing international conditions. Thus, during the 90s, the intensification of trade liberalization was combined with the privatization of key sectors of the economy (like the electricity and telecommunications sectors), resulting in structural changes, with the liberalization of capital flows and with a stabilization program (Plano Real), based on an exchange rate anchor, with important effects on the entire economy. Within this context, this article aims is to assess the evolution of external dependence and changes in terms of generating value added sectors of the Brazilian economy in the period 1995-2009, divided into three periods, namely, 1995-2000, 2000 - 2005 and 2005-2009. The database are the input-output Brazil annual matrices for the period 1995-2009, structured into 42 sectors, from which traditional Hirschman-Rasmussen indicators are calculated. The evolution of these indices is, then, combined with the coefficients of value added and imported inputs over time, allowing for a new treatment of intersectoral production multipliers. Preliminary results indicated a very satisfactory behavior of the national economy over time, with a predominance of positive gains in the ability to generate value added and lower imports of intermediate inputs by industries of medium and high technology, and less losses resulting growth the change in value added sector and greater external dependence for the minority of other sectors, particularly in recent years. It is hoped, with the development of the study to evaluate in detail the behavior of the 42 sectors in which Brazil's economy is structured in the study period.
Keywords: 330; structural changes; external vulnerabilities; regional economy